2021
DOI: 10.3390/su13105643
|View full text |Cite
|
Sign up to set email alerts
|

Trilemma of Nordic–Baltic Forestry—How to Implement UN Sustainable Development Goals

Abstract: Forests are the dominant land cover in Nordic–Baltic countries, and forestry, the management of forests for improved ecosystem-service (ES) delivery, is an important contributor to sustainability. Forests and forestry support multiple United Nations Sustainability Goals (UN SDGs) and a number of EU policies, and can address conflicting environmental goals. Forests provide multiple ecosystem services and natural solutions, including wood and fibre production, food, clear and clean water and air, animal and plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 76 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…The Green Deal identifies a number of possibilities including simple “traffic light” approaches where indicators are colour coded red, yellow or green depending on severity (Futter et al 2016 ). Another approach would be to use the strategy exemplified by Högbom et al ( 2021 ) where scientific synthesis supported targeted communication with EU decision makers.…”
Section: Conceptual Model For Research Infrastructure Co-locationmentioning
confidence: 99%
See 3 more Smart Citations
“…The Green Deal identifies a number of possibilities including simple “traffic light” approaches where indicators are colour coded red, yellow or green depending on severity (Futter et al 2016 ). Another approach would be to use the strategy exemplified by Högbom et al ( 2021 ) where scientific synthesis supported targeted communication with EU decision makers.…”
Section: Conceptual Model For Research Infrastructure Co-locationmentioning
confidence: 99%
“…A holistic understanding of carbon dynamics in northern European forests requires multiple forms of knowledge. These include: current and future societal perspectives on the bioeconomy (Rakovic et al 2020 ); robust assessment of GHG fluxes (e.g., Chi et al 2019 ); quantification of ecosystem pressures (Vuorenmaa et al 2018 ); new insights into controls on ecosystem service delivery (Holmberg et al 2019 ; Laudon et al 2021 ); and possible policy responses (Venäläinen et al 2020 ; Högbom et al 2021 ). Synthesizing new knowledge across each of these areas is a prerequisite for meeting the ambitious demands of the European Green Deal.…”
Section: The Terrestrial Carbon Sink: What How and Whymentioning
confidence: 99%
See 2 more Smart Citations
“…Boreal forests are some of the most heavily exploited types of land-cover in these countries (Zhou et al 2021). The rapid expansion of onshore wind energy infrastructure in Nordic countries in the Fennoscandian region (Norway, Sweden, Finland) is expected include substantial installation in forests (Högbom et al 2021). Rehbein et al (2020) found that large wind parks already overlap with key biodiversity areas such as forests, and will continue to be developed in such areas, in Fennoscandia.…”
Section: Introductionmentioning
confidence: 99%